The role and mechanism of “eight famous herbals in Zhejiang” in cancer via network pharmacology and experimental validation - Ni, Ziheng; Zhang, Hao; Chen, Fengyun; Yang, Mengjie; Yang, Liting; Zhou, Yuan; Zhou, Xianmin; Guo, Jiayi; Rao, Xinyu; Cen, Jiaqi; Lv, Qun; Wang, Jianjun; et al. (Frontiers in Oncology, 2024)
In recent years, some components and active ingredients from the herbal formula “eight famous herbals in Zhejiang” (Zhe-Ba-Wei) have been reported to possess antitumor properties. However, there is still no systemic study on the role and mechanism of Zhe-Ba-Wei in cancer. To systematically investigate the anticancer efficacy of Zhe-Ba-Wei, we first identified 17 reported active ingredients with gene targets associated with various types of tumors. Second, we screened these active ingredients and their responding multiple shared targets by analyzing the convergence of diverse and tumor-specific target sites and identified four crucial active ingredients (ferulic acid, quercetin, rutin, luteolin), which were characterized by 27 overlapping gene targets. Third, these 27 gene targets were subsequently mapped onto the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway and Gene Ontology term, and among the 27 total potential targets, 12 were involved in plasma membrane function. Fourth, we investigated the binding affinities between the four crucial active ingredients and their potential targets such as EGFR and MET, both of which are well-known oncogenes in various cancers. Subsequently, an investigation of the computational ADMET properties showed that most of these four ingredients exhibited good ADMET properties. Finally, we found that three active ingredients (ferulic acid, luteolin, and quercetin) could inhibit the proliferation of non-small cell lung cancer cells and decrease the protein expression of EGFR in a concentration-dependent manner. All these results shed light on the bioactive components, pharmacological effects, and drug development and utilization of Zhe-Ba-Wei, aiming to provide useful support for its further research and clinical application.